Efeitos neurocomportamentais e no estresse oxidativo em ratos tratados com extrato etanólico de própolis amarela - SILVEIRA, Cinthia Cristina Sousa de Menezes da (Universidade Federal do Pará, 2017)
Propolis is a resinous substance produced by bees that collect raw material from different parts of plants, through the addition of salivary secretions and wax. In Brazil, 13 types of propolis were chemically characterized. In the yellow propolis of Mato Grosso do Sul were identified 15 compounds, all belonging to the class of triterpenoids, and low levels of phenolic compounds and flavonoids. This work aims to conduct behavioral and biochemical assays with acute administration of yellow propolis ethanolic extract. 8 groups of male Wistar rats, 3 months, were used (n = 10 per group) and were divided into control (Tween 5%), positive control for anxiolytic activity (diazepam), positive control for antidepressant activity (fluoxetine), positive control for mnemonic effect (caffeine), 4 doses of the extract (1, 3, 10, 30mg/kg). The extract administration was performed acutely, intraperitoneally. Behavioral tests were open field, elevated plus maze, forced swimming and inhibitory avoidance. After the behavioral testing was performed to collect blood in the intracardiac area of the animals for determination of nitric oxide, malondialdehyde, catalase, superoxide dismutase and total antioxidant capacity. The results obtained in the open field test showed spontaneous locomotion preserved and anxiolytic-like activity, confirmed result with the elevated plus maze. In the forced swimming test, the yellow propolis ethanolic extract demonstrated action of antidepressant-like. In the inhibitory avoidance test showed mnemonic activity at 30 mg/kg. In the evaluation of oxidative biochemistry, the extract reduced the production of nitric oxide and malondialdehyde without changing level of total antioxidant, catalase and superoxide dismutase, induced by stress. With these results it is concluded that the yellow propolis ethanolic extract has anxiolytic, antidepressant, mnemonic and antioxidant activity.